On the ascent-descent spectrum - Athmouni, N.; Damak, M.; Jendoubi, C. (Methods of Functional Analysis and Topology, 2021)
We establish various properties as well as diverse relations of the ascent and descent spectra for bounded linear operators. We specially focus on the theory of subspectrum. Furthermore, we construct a new concept of convergence for such spectra. Встановлюються різні властивості спектрів підйому та спуску для обмежених лінійних операторів, а також певні співвідношення між ними. Ми зосереджуємося на теорії підспектру. Крім того, ми пропонуємо нове поняття збіжності для таких спектрів.